Workplace musculoskeletal problems in occupational therapy students - Joanne Morabito; Stefania Penkala; Kristy Coxon (BMC, 2021)
Abstract Background Workplace musculoskeletal disorders are the leading cause of morbidity and disability in the Australian workforce. Over one in five occupational therapists report workplace musculoskeletal disorders, with almost half reporting workplace musculoskeletal symptoms. In other health professions, students and novice clinicians (≤5 years practice) experience greater risk but little is known about occupational therapy students. Methods In this cross-sectional study, a survey including the self-reported Standardised Nordic Musculoskeletal Questionnaire was administered to occupational therapy students post work-based training. Musculoskeletal problems were defined as aches, pains, numbness or discomfort. Questions explored body sites affected, prevalence, impact on activity, need for medical assistance, demographic and workplace information. Prevalence was reported using descriptive statistics. Factors associated with workplace musculoskeletal problems over the previous 12 months and last 7 days were examined using logistic regression modelling. Results Response rate was 53% (n = 211/397). One-third of respondents (33.6%, n = 71/211) reported a workplace musculoskeletal problem over 12 months. Nearly half (47.9%, n = 34/71) of these students reported a problem over the last 7 days. Neck was the most commonly affected area reported for musculoskeletal problems over the past 12 months (24.2%, n = 51/211) and shoulder areas affected over the past 7 days (10.9%, n = 23/211). Musculoskeletal problems preventing daily activities were reported most commonly from lower back problems over 12 months (23.9%, n = 17/71) and for shoulder problems over the last 7 days (21.9%, n = 7/32). Shoulders and knees were the most common body areas requiring medical attention. Previous musculoskeletal problems and female gender were associated with reported problems over 12 months and last 7 days (p < 0.05). Non-standard joint mobility (OR = 3.82, p = 0.002) and working in psychosocially focused caseloads (including mental health or case management) (OR = 3.04, p = 0.044) were also associated with reporting musculoskeletal problems over the last 7 days. Conclusions One in three occupational therapy students already experience workplace musculoskeletal problems impacting daily activities and requiring medical assistance prior to graduation. High prevalence of musculoskeletal problems in this study calls for educators and researchers to find sustainable strategies to address these problems, with particular consideration to the impact of previous disorders and working in psychosocially focused caseloads on musculoskeletal health.